Androgen Deprivation Therapy and the Risk of Dementia after Treatment for Prostate Cancer. Issue 4 (2nd April 2022) - Lonergan, Peter E.; Washington, Samuel L.; Cowan, Janet E.; Zhao, Shoujun; Broering, Jeanette M.; Cooperberg, Matthew R.; Carroll, Peter R.
Abstract : Purpose: The association between androgen deprivation therapy (ADT) and dementia in men with prostate cancer remains inconclusive. We assessed the association between cumulative ADT exposure and the onset of dementia in a nationwide longitudinal registry of men with prostate cancer. Materials and Methods: A retrospective analysis of men aged ≥50 years from the CaPSURE (Cancer of the Prostate Strategic Urologic Research Endeavor) registry was performed. The primary outcome was onset of dementia after primary treatment. ADT exposure was expressed as a time-varying independent variable of total ADT exposure. The probability of receiving ADT was estimated using a propensity score. Cox proportional hazards regression was performed to determine the association between ADT exposure and dementia with competing risk of death, adjusted for propensity score and clinical covariates among men receiving various treatments. Results: Of 13, 570 men 317 (2.3%) were diagnosed with dementia after a median of 7.0 years (IQR 3.0–12.0) of followup. Cumulative ADT use was significantly associated with dementia (HR 2.02; 95% CI 1.40–2.91; p <0.01) after adjustment. In a subset of 8, 506 men, where propensity score matched by whether or not they received ADT, there was also an association between ADT use and dementia (HR 1.59; 95% CI 1.03–2.44; p=0.04). There was no association between primary treatment type and onset of dementia in the 8, 489 men in the cohort who did not receive ADT. Conclusions: Cumulative ADT exposure was associated with dementia. This increased risk should be accompanied by a careful discussion of the needs and benefits of ADT in those being considered for treatment.